Older people's aspirations for the aftermath of COVID-19: Findings from the WISE study. (20th October 2021) - Guzman, V; Pertl, M; Doyle, F; Foley, R
Abstract: Background: For many older people around the globe, the COVID-19 pandemic has highlighted accessibility issues and pervasive inequalities across multiple social, economic and health dimensions. The aim of the present study is to explore older people's perspectives about what we should learn from this pandemic and how to build a better future. Methods: The Well-being, Interventions and Support during Epidemics (WISE) study is an exploratory qualitative project that has collected information from 46 individuals aged 65+, who live in Irish community settings. Data collection included in-depth interviews over the phone or videoconference platforms. Analysis is ongoing utilizing NVivo12 to identify themes and linkages within a socio-ecological framework. Preliminary Results: Findings indicate that at the macrosystems level, several participants expect policymakers and researchers to commit to challenging ageist misconceptions of a homogeneous aging experience- such as the notion that older people are merely recipients of care with a high degree of needs. Upon reflection of their experiences with shelter-in-place restrictions and its consequences, at the exosystem level, many respondents called for older voices to be consulted in public health decisions and included in decision-making bodies. Concerning the microsystem, participants referred policymakers should further develop natural and built environments that enable physical, mental and social well-being for all. Cutting across all levels, participants advised for stronger political will and accountability, as they recognized some of their concerns had been addressed in past policies but were not being implemented. Conclusions: Our preliminary findings are applicable to the Irish context but also provide relevant insights for those interested in creating inclusive age-friendly societies across the globe. Embracing this shared vision would provide significant opportunities to address present and future public health challenges. Key messages: Older people are very diverse, so it is necessary to move on from one size fits all approaches. Age-friendly societies are multifaceted endeavours that must include older voices at their core and build upon intergenerational solidarity.